Interrelation of Natural Polyphenol and Fibrosis in Diabetic Nephropathy - Ye Ma; Jiakun Wang; Juyue Fan; Huiyang Jia; Jinyao Li (Molecules)
Diabetic nephropathy (DN) is a common and serious complication of diabetes mellitus and a major cause of end-stage renal disease (ESRD). Renal fibrosis, which corresponds to excessive deposition of extracellular matrix and leads to scarring, is a characteristic feature of the various progressive stages of DN. It can trigger various pathological processes leading to the activation of autophagy, inflammatory responses and a vicious circle of oxidative stress and inflammation. Although it is known that DN can be alleviated by mechanisms linked to antioxidants, reducing inflammation and improving autophagy, how to improve DN by reducing fibrosis using natural polyphenols needs to be studied further. Nowadays, natural polyphenolic compounds with excellent safety and efficacy are playing an increasingly important role in drug discovery. Therefore, this review reveals the multiple mechanisms associated with fibrosis in DN, as well as the different signaling pathways (including TGF-β/SMAD, mTORC1/p70S6K, JAK/STAT/SOCS and Wnt/β-catenin) and the potential role in the fibrotic niche. In parallel, we summarize the types of polyphenolic compounds and their pharmacodynamic effects, and finally evaluate the use of polyphenols to modulate relevant targets and pathways, providing potential research directions for polyphenols to improve DN. In summary, the problem of long-term monotherapy resistance can be reduced with natural polyphenols, while reducing the incidence of toxic side effects. In addition, potential targets and their inhibitors can be identified through these pathways, offering potential avenues of research for natural polyphenols in the pharmacological treatment of multisite fibrosis.